2006
DOI: 10.1097/01.hjh.0000226196.67052.c0
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid attenuates hypertension and improves endothelial function in spontaneously hypertensive rats

Abstract: Dietary CQA reduces oxidative stress and improves nitric oxide bioavailability by inhibiting excessive production of reactive oxygen species in the vasculature, and leads to the attenuation of endothelial dysfunction, vascular hypertrophy, and hypertension in spontaneously hypertensive rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
141
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(152 citation statements)
references
References 36 publications
5
141
0
6
Order By: Relevance
“…We cannot therefore exclude the fact that the same amount of caffeine might produce additional negative effects on endothelial function when ingested with other commercial beverage preparations different from coffee that do not contain antioxidants (Frary et al, 2005). Both animal (Suzuki et al, 2006) and human (Esposito et al, 2003) studies have shown that antioxidants improve endothelial function. In fact, antioxidants are also present in chocolate, which can be rich in flavanols (polyphenols) known to increase FMD and affect endothelial dysfunction (Grassi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot therefore exclude the fact that the same amount of caffeine might produce additional negative effects on endothelial function when ingested with other commercial beverage preparations different from coffee that do not contain antioxidants (Frary et al, 2005). Both animal (Suzuki et al, 2006) and human (Esposito et al, 2003) studies have shown that antioxidants improve endothelial function. In fact, antioxidants are also present in chocolate, which can be rich in flavanols (polyphenols) known to increase FMD and affect endothelial dysfunction (Grassi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Chlorogenic acids may contribute to these antihypertensive effects. Suzuki et al 24 conducted an experiment in spontaneously hyperactive rats, and hypothesized that the mechanism underlying the hypotensive action of chlorogenic acids is as follows: the ingestion of chlorogenic acids may inhibit the excessive synthesis of ROS, decreasing the blood pressure via improvement in NO availability in vivo and in vascular endothelial function. This hypothesis is supported by results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…8,9) It is known that CGA has many biological effects, such as anti-inflammation, antioxidation, and antihypertension effects. 10) It has been reported that CGA could suppress inflammatory factors and attenuate remodeling of liver ischemic injury in mice. 11) Although they are well documented, their effects on MI have yet to be investigated.…”
mentioning
confidence: 99%